INNOVATIVE TECHNOLOGIES FOR ENHANCING THE EFFECTIVENESS OF PEDAGOGICAL PROCESSES IN GENERAL SECONDARY SCHOOLS - Toyev Bakhtiyor Zarifovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
The rapid development of information and communication technologies has significantly transformed educational systems worldwide. In general secondary schools, the integration of innovative technologies into pedagogical processes has become an essential strategy for improving educational quality, student engagement, and learning outcomes. Innovative technologies provide opportunities for personalized learning, collaborative knowledge construction, and effective assessment practices. They facilitate interactive learning environments where students actively participate in educational activities rather than remaining passive recipients of information. The implementation of digital platforms, artificial intelligence, virtual and augmented reality, learning management systems, and gamification techniques has demonstrated considerable potential in enhancing teaching effectiveness and student achievement.